IMPLEMENTASI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA DAN RAHMATAN LIL'ALAAMIN DALAM PEMBELAJARAN: STUDI KAJIAN DI SMA 3 KOTA JAMBI - Oktarina, Yulia; Sururudin (Jurnal Muara Pendidikan, 2025)
The implementation of P5RA in Islamic Religious Education (PAI) and Character Education at SMA Negeri 3 Jambi City is still in the adaptation stage and requires a more structured strategy to achieve holistic educational goals in line with the Merdeka Curriculum. This study employed a qualitative approach with a descriptive method, conducted at SMA Negeri 3 Jambi City. The research subjects consisted of the principal, homeroom teachers, Islamic Religious Education and Character Education teachers, as well as students. Data were collected through interviews, observations, and documentation, and analyzed using qualitative techniques, including data reduction, data presentation, and conclusion drawing. The findings indicate that: (1) the planning of P5RA in PAI learning emphasizes the integration of Pancasila values and Islamic teachings into students’ daily lives. Teachers designed activities that encourage the practice of values such as cooperation, tolerance, empathy, justice, and environmental awareness through both theoretical and practical approaches; (2) the implementation of P5RA is carried out by embedding Pancasila values and Islamic teachings into daily learning activities using collaborative and socially oriented methods; and (3) the evaluation of P5RA implementation is comprehensive, employing various models such as formative, summative, self-assessment, and portfolio evaluations. These results highlight the need for continuous commitment from all school stakeholders to refine the implementation of P5RA in PAI learning at SMA Negeri 3 Jambi City.